Hybrid Sharia Contracts in Islamic Banking: Legal Validity and Sharia Compliance in Indonesian Religious Court Judgments - Zeis Zultaqawa; Joni Harianto; Yaumi Sidik Ginanjar; Mohamad Donie Aulia; Wahyudi Wahyudi (Universitas Muhammadiyah Bandung, 2025)
The rapid growth of Islamic banking in Indonesia has encouraged financial product innovation, particularly through the application of hybrid sharia contracts that combine two or more contracts within a single transaction structure. Although such contracts are normatively recognized in fiqh muamalah and explicitly permitted under fatwas issued by the National Sharia Council of the Indonesian Ulama Council (DSN-MUI), judicial practice reveals inconsistent assessments regarding their legal validity. This study aims to examine the legal validity of hybrid sharia contracts from the perspective of Religious Court decisions and to analyze the juridical implications of sharia non-compliance in hybrid contractual arrangements. Employing a normative juridical method with a descriptive-analytical approach, this research analyzes primary legal materials in the form of Religious Court judgments, alongside secondary legal sources including legislation, scholarly works, and DSN-MUI fatwas, using qualitative legal analysis. The findings indicate that hybrid sharia contracts are legally valid in principle, provided that they fulfill the essential elements and conditions of contracts, avoid prohibited elements such as riba, gharar, and maisir, and are implemented in strict accordance with DSN-MUI fatwas. However, Religious Court decisions demonstrate that ambiguity in the classification and sequencing of contracts, imbalanced risk allocation that departs from profit-and-loss sharing principles, and deviations from DSN-MUI fatwas result in hybrid contracts being deemed defective or invalid both sharia-wise and legally binding. These deficiencies not only undermine the juridical validity of contracts but also pose risks to public trust and confidence in Islamic banking institutions. Accordingly, DSN-MUI fatwas function as a crucial source of substantive law and serve as the primary benchmark for Religious Court judges in assessing the legality and sharia compliance of hybrid sharia contracts.